2010
DOI: 10.1038/ng.570
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the RAD51C gene in a Fanconi anemia–like disorder

Abstract: Fanconi anemia (FA) is a rare chromosomal-instability disorder associated with a variety of developmental abnormalities, bone marrow failure and predisposition to leukemia and other cancers. We have identified a homozygous missense mutation in the RAD51C gene in a consanguineous family with multiple severe congenital abnormalities characteristic of FA. RAD51C is a member of the RAD51-like gene family involved in homologous recombination-mediated DNA repair. The mutation results in loss of RAD51 focus formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
323
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(337 citation statements)
references
References 30 publications
7
323
1
6
Order By: Relevance
“…However, no hematological abnormalities or cancers were diagnosed in the children. Sequencing results confirmed the homozygous missense mutation (G773A, R258H) in RAD51C exon 5, and RAD51C has been assigned as FANCO, a 14th in the FA family genes (18,38). In a parallel study, monoallelic mutations in RAD51C were identified to cause breast and ovarian cancers.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…However, no hematological abnormalities or cancers were diagnosed in the children. Sequencing results confirmed the homozygous missense mutation (G773A, R258H) in RAD51C exon 5, and RAD51C has been assigned as FANCO, a 14th in the FA family genes (18,38). In a parallel study, monoallelic mutations in RAD51C were identified to cause breast and ovarian cancers.…”
mentioning
confidence: 51%
“…In a striking observation, germ line mutations in RAD51C have been identified to cause FA-like disorder and breast and ovarian cancers (38,39). Biallelic mutation in RAD51C was identified in a family with a characteristic phenotype of FA.…”
mentioning
confidence: 99%
“…RAD51C maintains genome integrity by participating in branch migration and Holliday junction resolution (12,13,27). Germline mutations in RAD51C confer an increased risk of breast and ovarian cancer (28)(29)(30). According to the previous studies, the role of RAD51C in homologous recombination activation via the regulation of RAD51 recruitment was understood.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous other physiological and cellular abnormalities likely contribute to pathogenesis (Figure 1). The current decade has been prolific for the discovery of novel FA genes Thus, seventeen genes are associated to FA, including the recently discovered genes FANCO/RAD51C [1], FANCP/SLX4 [2,3], FANCQ/ERCC4 [4], and FANCS/BRCA1 [5]. However, following the stringent criteria of at least 2 patients with BMF and a positive chromosome fragility test, only 14 met the criteria for bona fide…”
Section: Introduction: Fanconi Anemia and Fanconi Anemia-like Genesmentioning
confidence: 99%